Evaluation of Conventional Treatment Planning Techniques for Radiotherapy of Gastroesophageal Junction Cancer: A Dosimetric Comparison between Male and Female Patients - Mohamad Pursamimi; Mahdi Ghorbani; Mehdi Khosravi; Ghazal Mehri-Kakavand; Wrya Parwaie; Seyed Mohammad Hosseini; Ali Mohammad Sharifi; Meysam Tavakoli (Frontiers in Biomedical Technologies)
Gastro-Esophageal (GE) junction cancer has been increasingly prevalent worldwide. This study aims to compare dosimetric and radiobiological parameters for target areas and Organs At Risk (OARs) in men and women patients diagnosed with GE junction cancer.